Marchesini, R. (2023). Posthumanist Manifesto. Lexington. - Hay, Jonathan (Journal of Posthumanism, 2024)
Although it is often frustrating, Roberto Marchesini’s Posthumanist Manifesto makes a number of valuable contributions to Critical Posthumanist discourse. The extent to which it questions many of the accepted principles in the discipline renders it a challenging read, but one which should be rewarding for those scholars who take the time to parse its depths. The verbosity of the whole is incipiently apparent in its opening, whereupon Marchesini proposes that ‘Hybridization is the moment of the Appollonian becoming while staying within a Dionysian flow of possibilities and transitions’ (2). As here, the Manifesto dispels copious amounts of intelligent reflection across its thirty constituent theses. It rarely takes the time for definition, operating on the assumption that its readers will be familiar with a broad range of highly technical vocabulary and concepts.